2008
DOI: 10.1055/s-2008-1077619
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic resection of sporadic duodenal adenomas: an efficient technique with a substantial risk of delayed bleeding

Abstract: Endoscopic resection is an efficient and acceptably safe technique for treating SDA. Further studies need to assess whether systematic bleeding prophylaxis will reduce the incidence of delayed hemorrhage after endoscopic resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
116
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(125 citation statements)
references
References 11 publications
7
116
0
2
Order By: Relevance
“…23 Therefore, there have been only a few studies on duodenal EMR over a small number of patients. 13,[15][16][17][18][19] In the present study, the standard inject-and-cut EMR technique was used to treat the duodenal adenomas. The largest tumor resected by this method was 27 mm in diameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Therefore, there have been only a few studies on duodenal EMR over a small number of patients. 13,[15][16][17][18][19] In the present study, the standard inject-and-cut EMR technique was used to treat the duodenal adenomas. The largest tumor resected by this method was 27 mm in diameter.…”
Section: Discussionmentioning
confidence: 99%
“…14 Since then several studies have reported endoscopic resection as a safe and effective alternative to surgery in patients with benign duodenal adenomas and for those that were poor surgical candidates. 13,[15][16][17][18][19] However, data on the adequacy of the resection and long-term outcomes are limited. This study evaluated the efficacy and long-term endos- copy findings in a cohort of Korean patients that underwent endoscopic excision of sporadic nonampullary duodenal adenomas.…”
Section: Introductionmentioning
confidence: 99%
“…Usually intra-procedure in gastric lesions, occurring in 3.4% to 7.2% and delayed in duodenum, reported in 3.1%-22% of patients [2,26]. In colorectal polypectomy, bleeding occurs in 0.3% to 6.1% [27].…”
Section: Polypectomymentioning
confidence: 99%
“…Benefits of duodenal ESD seem marginal comparing to EMR, with the exception of small-medium size encapsulated submucosal tumors (NET, for example), in which endoscopic ultrasound (EUS) has excluded muscularis propria layer infiltration or locoregional lymph nodes involvement. The most frequent complication is bleeding (53). It is important to perform preventive vessel coagulation with coagulation forceps, argon plasma or bipolar catheter.…”
Section: Duodenummentioning
confidence: 99%